Exploring the safe and just space for urban and regional Australia - Kylie Goodwin; Mengyu Li; Thomas Wiedmann (npj Urban Sustainability)
Abstract Australia is a highly urbanised country, with over 85% of people living in city environments, so the lifestyles of city dwellers and the infrastructure of cities are critical to addressing sustainability issues. Australian cities have embraced the Doughnut Economics framework for sustainability; however, methodologies and data to comprehensively assess environmental and social sustainability are underdeveloped and locally focused, undermining the effectiveness of targets set. This research compares social outcomes of capital cities and regional areas within Australia with 12 environmental stressors and shows that consumption-based, environmental footprints are between 1.7 and 44 times higher than global averages. The most critical environmental issue is biodiversity loss within Australia while the most critical social issues are living standards in remote and regional communities, and inequality. The sustainability challenges for different actors, planetary boundaries, and economic sectors in Australia vary substantially, especially when viewed from a consumption rather than a production perspective.